Advances and challenges in cirrhosis and portal hypertension - Berzigotti, Annalisa (BMC Med, 2017)
BACKGROUND: Liver cirrhosis is the fourth cause of death in adults in Western countries, with complications of portal hypertension being responsible for most casualties. In order to reduce mortality, development of accurate diagnostic methods for early diagnosis, effective etiologic treatment, improved pharmacological therapy for portal hypertension, and effective therapies for end-stage liver failure are required. DISCUSSION: Early detection of cirrhosis and portal hypertension is now possible using simple non-invasive methods, leading to the advancement of individualized risk stratification in clinical practice. Despite previous assumptions, cirrhosis can regress if its etiologic cause is effectively removed. Nevertheless, while this is now possible for cirrhosis caused by chronic hepatitis C, the incidence of cirrhosis due to non-alcoholic steatohepatitis has increased dramatically and effective therapies are not yet available. New drugs acting on the dynamic component of hepatic vascular resistance are being studied and will likely improve the future management of portal hypertension. CONCLUSION: Cirrhosis is now seen as a dynamic disease able to progress and regress between the compensated and decompensated stages. This opinion article aims to provide the author’s personal view of the current major advances and challenges in this field.